Bending of elastic plates with transverse shear deformation: The Neumann problem. (9th January 2018) - Constanda, Christian; Doty, Dale
Abstract : A generalized Fourier series method is constructed to approximate the solution of the Neumann problem in a finite domain for the system of equations governing the bending of elastic plates with transverse shear deformation. The method is illustrated by an example with computation performed by 3 different techniques that are contrasted and compared for efficiency, accuracy, and stability.